Engineering of transition metal-assisted graphene and carbon nanotubes formation in transmission electron microscopy - Mohamad Saufi Rosmi (N/A, 2017)
Engineering of transition metal-assisted graphene and carbon nanotubes formation in transmission electron microscopy by Mohamad Saufi Rosmi